Determinants of foreign inflows from current transfers into Barbados - Campbell, Trevor (2003)
Shows that in the long run, current transfers are influenced by real foreign income, real local income, long-stay tourist arrivals, dividend income payments abroad and the real exchange rate. Illustrates that in the short run, current transfer inflows are influenced by its previous levels, real foreign income, real local income, long-stay tourist arrivals and real exchange rates. Examines the policy implications of these results.